How can we reconcile the following apparent truths: ‘Sherlock Holmes doesn’t exist’ and ‘Sherlock Holmes was created by Conan Doyle’? - Tim Short (Opticon1826, 2014)
I will argue that the two statements can be reconciled by Parsons's view which is inspired by a Meinongian ontology. I will assume these views together with Parsons's classification of fictional properties as ‘nuclear’ and ‘extra-nuclear’. This division of properties into types eliminates the requirement for the view to associate an object with a set of properties {goldenness, mountain-hood, existence} which is important as there is no existent golden mountain. I will throughout use italics for the names of properties and braces for sets. The titular question is a well-known problem for views of ficta since it appears that we believe both claims are true but they seem to be inconsistent. I understand 'ficta' to be any object or person described in fiction. I will argue that we can resolve the tension by adopting Parsons's view of ficta.